ADSC Exosomes Mediate lncRNA-MIAT Alleviation of Endometrial Fibrosis by Regulating miR-150-5p - Shao, Xiaowen; Qin, Jinlong; Wan, Chendong; Cheng, Jiajing; Wang, Lian; Ai, Guihai; Cheng, Zhongping; Tong, Xiaowen (Frontiers in Genetics, 2021)
Background. Secondary infertility remains a major complication of endometrial fibrosis in women. The use of exosomes from adipose-derived mesenchymal stem cells (ADSCs) has shown promising results for the treatment of endometrial fibrosis. However, the mechanisms of action of ADSC-exosome (ADSC-Exo) therapy remain unclear. Methods. An endometrial fibrosis model was established in mice treated with alcohol and endometrial epithelial cells (ESCs) treated with TGF-β1. ADSCs were isolated from Sprague Dawley (SD) rats, and exosomes were isolated from ADSCs using ExoQuick reagent. Exosomes were identified by transmission electron microscopy (TEM), NanoSight, and Western blot analysis. The expression level of lncRNA-MIAT was detected by qPCR analysis. Western blot analysis was carried out to determine the protein levels of fibrosis markers (TGFβR1, α-SMA and CK19). A dual-luciferase reporter gene assay was used to verify the relationship between target genes. The endometrial tissues of the endometrial fibrosis model were stained with HE and Masson’s trichrome. Results. ADSCs and ADSC-Exos were successfully isolated, and the expression level of lncRNA-MIAT was significantly down-regulated in endometrial tissue and the TGF-β1-induced ESC injury model, whereas ADSC-Exos increased the expression of lncRNA-MIAT in the TGF-β1-induced ESC model. Functionally, ADSC-Exo treatment repressed endometrial fibrosis in vivo and in vitro by decreasing the expression of hepatic fibrosis markers (α-SMA and TGFβR1) and increasing the expression of CK19. Moreover, miR-150-5p expression was repressed by lncRNA-MIAT in the TGF-β1-induced ESC injury model. The miR-150-5p mimic promoted TGF-β1-induced ESC fibrosis. Conclusions. ADSC-Exos mediate lncRNA-MIAT alleviation of endometrial fibrosis by regulating miR-150-5p, which suggests that lncRNA-MIAT from ADSC-Exos may be a viable treatment for endometrial fibrosis.